ANALISIS PERBANDINGAN KINERJA KEUANGAN BANK PEMERINTAH DAN BANK SWASTA - Renny Mointi (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2019)
This study aims to analyze the comparison of the financial performance of government banks and private bank on PT. Bank Negara Indonesia (Persero) and PT. Bank Central Asia (Persero) tbk period 2015-2017. As for the analytical tool used is the independent sample test by assessing CAR Ratio, NPL, ROA, BOPO and LDR. The result of the research shows that there is no significant effect to the ROA, Ratio, BOPO and LDR on PT. Bank Negara Indonesia (Persero) tbk and PT. Bank Central Asia (Persero)tbk.